The gifted passage : young men in classic Maya art and text - Houston, Stephen D. (Yale University Press, 2018)
"In this thought-provoking book, preeminent scholar Stephen Houston turns his attention to the crucial role of young males in Classic Maya society, drawing on evidence from art, writing, and material culture. The Gifted Passage establishes that adolescent men in Maya art were the subjects and makers of hieroglyphics, painted ceramics, and murals, in works that helped to shape and reflect masculinity in Maya civilization. The political volatility of the Classic Maya period gave male adolescents valuable status as potential heirs, and many of the most precious surviving ceramics likely celebrated their coming-of-age rituals. The ardent hope was that youths would grow into effective kings and noblemen, capable of leadership in battle and service in royal courts. Aiming to shift mainstream conceptions of the Maya, Houston argues that adolescent men were not simply present in images and texts, but central to both."--